The Effect Of Quality And Service Features On Customer Satisfaction Of The AT-TAUSIL Application (Study On Customers Of Barru District) - Syahrul Safar; Andi Muhammad Rivai; Didin Halim; Fatimah Akbal (Fakultas Ilmu Sosial dan Hukum, 2024)
The Effect of Quality and Service Features on Customer Satisfaction of the At-Tausil Application (Study on Barru District Customers). Thesis. Business Administration Study Program. Department of Administrative Sciences. Faculty of Social Sciences and Law. Makassar State University. (Guided by Muhammad Guntur and Didin Halim). This study aims to find out how the effect of service quality and service features on customer satisfaction of the At-Tausil Application simultaneously and partially where at-Tausil Application users who are domiciled in Barru district are the object of their research. This research uses a quantitative type of research. The data collection techniques used are through primary data collection (observations and questionnaires) and secondary data collection (literature and documentation review). The sample used was the sample formulated by Slovin, which was 97 respondents. The results of this study show that partially, service quality variables affect customer satisfaction, and service features have no effect on customer satisfaction of the At-Tausil Application. Meanwhile, simultaneously the quality and features of the service affect the customer satisfaction of the At-Tausil Application.